Liver Transplantation as a New Standard of Care in Patients With Perihilar Cholangiocarcinoma? Results From an International Benchmark Study. Issue 5 (27th November 2022) - Breuer, Eva; Mueller, Matteo; Doyle, Majella B.; Yang, Liu; Darwish Murad, Sarwa; Anwar, Imran J.; Merani, Shaheed; Limkemann, Ashley; Jeddou, Heithem; Kim, Steven C.; López-López, Victor; Nassar, Ahmed; et al.
Abstract : Objective: To define benchmark values for liver transplantation (LT) in patients with perihilar cholangiocarcinoma (PHC) enabling unbiased comparisons. Background: Transplantation for PHC is used with reluctance in many centers and even contraindicated in several countries. Although benchmark values for LT are available, there is a lack of specific data on LT performed for PHC. Methods: PHC patients considered for LT after Mayo-like protocol were analyzed in 17 reference centers in 2 continents over the recent 5-year period (2014–2018). The minimum follow-up was 1 year. Benchmark patients were defined as operated at high-volume centers (≥50 overall LT/year) after neoadjuvant chemoradiotherapy, with a tumor diameter <3 cm, negative lymph nodes, and with the absence of relevant comorbidities. Benchmark cutoff values were derived from the 75th to 25th percentiles of the median values of all benchmark centers. Results: One hundred thirty-four consecutive patients underwent LT after completion of the neoadjuvant treatment. Of those, 89.6% qualified as benchmark cases. Benchmark cutoffs were 90-day mortality ≤5.2%; comprehensive complication index at 1 year of ≤33.7; grade ≥3 complication rates ≤66.7%. These values were better than benchmark values for other indications of LT. Five-year disease-free survival was largely superior compared with a matched group of nodal negative patients undergoing curative liver resection (n=106) (62% vs 32%, P <0.001). Conclusion: This multicenter benchmark study demonstrates that LT offers excellent outcomes with superior oncological results in early stage PHC patients, even in candidates for surgery. This provocative observation should lead to a change in available therapeutic algorithms for PHC.